2019
DOI: 10.1002/adfm.201906232
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Photocurrent via Heating BiFeO3 Materials for Enhanced Self‐Powered UV Photodetectors

Abstract: BiFeO 3 (BFO) is a potentially important Pb-free ferroelectric with a narrow bandgap and is expected to become a novel photodetector. The photocurrent in BFO 3 strongly depends on the temperature but only a few studies have investigated in detail the relationships between photocurrent and temperature. Here, the temperature-dependent photocurrent and the corresponding photosensing properties of a Ag/BFO/indiumtin oxide (ITO) photodetector based on an optimized planar-structured electrode configuration are inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 39 publications
0
49
0
Order By: Relevance
“…6d , PEPI exhibits obvious I sc signal in the wide range of 365–670 nm, which is consistent with its narrow optical absorption bandgap. Compared to traditional inorganic materials, such as ZnO 9 , BiFeO 3 35 , Pb(Zr,Ti)O 3 36 , and GaN 37 , PEPI possesses the wider self-driven detection range up to 670 nm. As far as we know, this figure-of-merit is the widest value obtained for the existing molecular ferroelectrics materials, which endows great potentials of PEPI toward broadband self-driven photodetection.…”
Section: Resultsmentioning
confidence: 99%
“…6d , PEPI exhibits obvious I sc signal in the wide range of 365–670 nm, which is consistent with its narrow optical absorption bandgap. Compared to traditional inorganic materials, such as ZnO 9 , BiFeO 3 35 , Pb(Zr,Ti)O 3 36 , and GaN 37 , PEPI possesses the wider self-driven detection range up to 670 nm. As far as we know, this figure-of-merit is the widest value obtained for the existing molecular ferroelectrics materials, which endows great potentials of PEPI toward broadband self-driven photodetection.…”
Section: Resultsmentioning
confidence: 99%
“…Adapted with permission from Ref. [ 115 ]. f BFO nanomaterials with different morphologies show different photocatalytic activities.…”
Section: Properties Of Bfomentioning
confidence: 99%
“…This work demonstrated that it is possible to modulate the photovoltaic performance by controlling temperature gradients, which can provide a novel pathway to enhance the photovoltaic property of BFO-based material. Then, they further deeply investigated the relationships between photocurrent and temperature [ 115 ]. As illustrated in Fig.…”
Section: Properties Of Bfomentioning
confidence: 99%
“…Examples of novel work reported in recent years are listed in Table 3 and Figure 6, where the output performance and figure of merit of these photovoltaic devices are summarized in Table 3. [51,160,162,[170][171][172][173] Inorganic ferroelectric materials with perovskite structure are often used in solar energy harvesting or photodetection. The bandgaps of typical perovskite materials are relatively wide (2.7-4 eV), which limits the photoabsorption capability of perovskite materials and only 8-20% of the solar spectrum can be absorbed.…”
Section: Ferroelectric Materials For Photovoltaic Devicesmentioning
confidence: 99%